Development of a Regional Stratigraphic Framework For Upper Devonian Reef Complexes Using Integrated Chronostratigraphy: Lennard Shelf, Canning Basin, Western Australia - Playton, T.; Hocking, R.; Montgomery, P.; Tohver, E.; Hillbun, K.; Katz, D.; Haines, P.; Trinajstic, Katherine; Yan, M.; Hansma, J.; Pisarevsky, S.; Kirschvink, J.; et al. (N/A, 2013)
Questions regarding heterogeneity and architecture of reefal carbonate platform systems may be resolved by well-constrained chronostratigraphic frameworks, developed from the integration of multiple independent signals in the rock record. This makes possible a meaningful comparison of coeval stratigraphy and facies in different settings. For the Canning Basin Chronostratigraphy Project (CBCP), key outcrop transects and shallow cores were logged for lithofacies and sampled at sub-meter scale for magnetostratigraphy, stable isotope chemostratigraphy, conodont-fish biostratigraphy, biomarker geochemistry, and elemental chemostratigraphy. The dataset entails nearly 4 km of measured stratigraphy and 6800 samples of Middle and Upper Devonian (Givetian, Frasnian and Famennian) carbonate platform-top, reef, foreslope, and basinal deposits along the Lennard Shelf, Canning Basin, Western Australia. The extracted rock signals were integrated in conjunction with sequence stratigraphic concepts to generate a multifacetted, regional chronostratigraphy and predictive lithofacies model across 250 km of the exposed Devonian reef complexes.Final results from the ongoing project will include: high-resolution, high-confidence correlations across different carbonate settings that were not achievable before using traditional biostratigraphy or sequence stratigraphic concepts; unprecedented examination of Lennard Shelf carbonate heterogeneity and architecture within the constrained framework; an integrated workflow for establishing robust chronostratigraphic frameworks that can be tailored for the subsurface; a magnetostratigraphic framework for parts of the Late Devonian (a period of uncertainty in the polarity reversal record), calibrated to biostratigraphic zones; and geochemical and elemental profiles that reflect sea level fluctuations, water column stratification/circulation, and biotic crises during deposition of the reef complexes. The integrated framework and predictive depositional model for the Devonian reef complexes will be a comprehensive product that serves as an analogue for carbonate researchers and petroleum geoscientists worldwide.